DAMPAK PERGAULAN BEBAS TERHADAP KEHAMILAN DI LUAR NIKAH - Salsabilla, Tiara; Syellen Edwid Nivacindera; Siti Maemunah; Nurkholisoh; Oyoh Bariyah (LPPM Universitas Al Muslim, 2025)
Promiscuity among teenagers and young adults has become a significant social issue, one of which is marked by the increasing number of extramarital pregnancies. Lack of understanding of sex education and low awareness of the long-term impacts of such behavior are the main factors influencing this phenomenon. This community service activity aimed to educate teenagers about the risks of promiscuity, related to unwanted pregnancies, through an interactive discussion-based counseling program. This activity was carried out at MTSN 2 Karawang by involving teenagers as the main participants. The method of implementing the activity used a qualitative approach through surveys, interviews, and observations in the counseling session. The results of the implementation of the activity showed that the main factors causing extramarital pregnancies were the influence of the media, weak social norms, and lack of knowledge about contraceptives. In addition, many teenagers are not aware of the physical and psychological health impacts of unplanned pregnancies. This counseling succeeded in increasing participants' awareness of the importance of sex education, moral values, and responsible relationship planning. Recommendations provided include strengthening school-based and community-based education to reduce the number of extramarital pregnancies and to create teenagers who are more aware of reproductive health.